2023
DOI: 10.1007/jhep03(2023)086
|View full text |Cite
|
Sign up to set email alerts
|

Non-singlet quark helicity PDFs of the nucleon from pseudo-distributions

Abstract: The non-singlet helicity quark parton distribution functions (PDFs) of the nucleon are determined from lattice QCD, by jointly leveraging pseudo-distributions and the distillation spatial smearing paradigm. A Lorentz decomposition of appropriately isolated space-like matrix elements reveals pseudo-distributions that contain information on the leading-twist helicity PDFs, as well as an invariant amplitude that induces an additional z2 contamination of the leading-twist signal. An analysis of the short-distance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 221 publications
0
0
0
Order By: Relevance
“…The leading order DGLAP evolution was first used in [5], where numerical evidence suggested that the quenched lattice QCD results for M(ν, z 2 ) indeed follow this evolution in z 2 . More generally, a wealth of numerical analyses have shown that for z < 0.2 ∼ 0.3 fm, various truncations of the perturbative matching give rather similar results, mostly compatible with the phenomenological knowledge of unpolarized PDFs [40,52,[58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75].…”
Section: Fitting a Non-perturbative Step-scaling Function To Lattice ...supporting
confidence: 61%
“…The leading order DGLAP evolution was first used in [5], where numerical evidence suggested that the quenched lattice QCD results for M(ν, z 2 ) indeed follow this evolution in z 2 . More generally, a wealth of numerical analyses have shown that for z < 0.2 ∼ 0.3 fm, various truncations of the perturbative matching give rather similar results, mostly compatible with the phenomenological knowledge of unpolarized PDFs [40,52,[58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75].…”
Section: Fitting a Non-perturbative Step-scaling Function To Lattice ...supporting
confidence: 61%
“…A recent calculation of the iso-vector helicity quark PDF was reported in Ref. [39] by the HadStruc Collaboration. A single lattice spacing a = 0.094 fm and slightly heavier than physical quark mass was used.…”
Section: Polarized Quark Pdfsmentioning
confidence: 99%